Developing Instructional Support for MEDSReM-2 Through Human Factors Design Principles. (17th December 2021) - Mitzner, Tracy; Harris, Maurita; Blocker, Kenneth; Trinh, Mimi
Abstract: Appropriate instruction is critical for ensuring the MEDSReM-2 system (i.e., smartphone app, blood pressure monitor, online portal) will be easily and effectively used and will, therefore, be more likely to be adopted. We will present our iterative processes for developing instructional support for MEDSReM 2 using human factors design principles (e.g., task analyses, comparative analyses, expert evaluation of mock-ups with screen flows). The instructional supports include user manuals, videos, as well as instructions within the MEDSReM 2 app. We will also highlight design principles used to empower the user and the benefits of using an interdisciplinary approach (i.e., gerontology, cognitive psychology, educational psychology, design, community health) to develop instructional support for older adult users.